AN ANALYSIS OF LOCUTIONARY AND ILLOCUTIONARY ACT OF REPRESENTATIVE UTTERANCES USED IN DIGITAL STORYTELLING: I’M AN ANIMAL SERIES BY BROWN BAG FILMS - Fristi Arfiawati; Rossantiana Agus Ramdani (Jurnal Sastra - Studi Ilmiah Sastra, 2020)
The research entitled An Analysis of  Locutionary and Illocutionary Act  of Representative Utterances Used in Digital Storytelling: I’m an Animal Series by Brown Bag Films aims to analyze the locutionary and Illocutionary act based on Austin’s theory and Searle’s theory in digital storytelling videos I’m an Animal series directed by Brown Bag Films. The research used descriptive qualitative method and the data were taken in the form of utterances spoken by the animals in digital storytelling videos, transcribed into the written form and then analyzed by using the theory of speech acts. The research focus on a representatives utterances as the animals mainly talk about their life.  The findings showed that there were several locutionary and Illocutionary act of representative utterances in the Digital Storytelling video of I’m an Animal Series by Brown Bag Film.